2005
DOI: 10.1016/j.diagmicrobio.2005.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 9 different PCR primers for the rapid detection of severe acute respiratory syndrome coronavirus using 2 RNA extraction methods

Abstract: The sensitivity and specificity of various severe acute respiratory syndrome coronavirus (SARS-CoV) PCR primer and probe sets were evaluated through the use of commercial kits and in-house amplification formats. Conventional and real-time PCR assays were performed using a heat-block thermocycler ABI 9600, the Roche LightCycler version 1.2, or the ABI 7000 Sequence Detection System. The sensitivity of all primers was between 0.0004 and 0.04 PFU with viral cell lysate and between 0.004 and 0.4 PFU in spiked stoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…The sensitivity of our method is similar to the sensitivity of other real-time PCR assays based on the ORF1b for the specific detection of SARS-CoV, including the commercial SARS-CoV Quantification kit (Roche, Penzberg, Germany) [6,7,19,22,25,27]. The RealArt HPA coronavirus LC kit (Artus, Hamburg, Germany) nevertheless seems to be more sensitive, with a detection level down to 0.5-1.5 SARS-CoV RNA copy per reaction [4]. Targeting the N gene has been postulated to be a better choice to improve the sensitivity of the PCR as this gene is supposed to have the most abundant copy number during viral replication [35].…”
Section: Discussionmentioning
confidence: 51%
“…The sensitivity of our method is similar to the sensitivity of other real-time PCR assays based on the ORF1b for the specific detection of SARS-CoV, including the commercial SARS-CoV Quantification kit (Roche, Penzberg, Germany) [6,7,19,22,25,27]. The RealArt HPA coronavirus LC kit (Artus, Hamburg, Germany) nevertheless seems to be more sensitive, with a detection level down to 0.5-1.5 SARS-CoV RNA copy per reaction [4]. Targeting the N gene has been postulated to be a better choice to improve the sensitivity of the PCR as this gene is supposed to have the most abundant copy number during viral replication [35].…”
Section: Discussionmentioning
confidence: 51%
“…The NML has maintained rigorous quality control since then, with no evidence of similar findings. Since 2003, there has been some effort to refine RT-PCR testing for SARS-CoV generally, and most experts now caution against the use of nested methods for routine diagnostic testing (35). The present investigation underscores the fact that laboratory testing is but one way to form inferences on the etiology of outbreaks, and cannot replace scrupulous clinical and epidemiological observation.…”
Section: Discussionmentioning
confidence: 82%
“…Similar approaches have implemented microfluidic platforms that can detect pathogenic avian influenza virus H5N1 in a throat swab sample. The technique coupled with polymerase chain reaction uses magnetic forces to manipulate a free droplet containing superparamagnetic particles . These approaches are so sensitive, as Mizutani et al showed, that they were able to isolate five particles from the influenza virus .…”
Section: Resultsmentioning
confidence: 99%